Study of the effect of composite constrained layers in vibration damping of plates - Sasikumar, K.S.K.; Selvakumar, S.; Arulshri, K.P. (Zielona Góra: Uniwersytet Zielonogórski)
To add damping to the system, viscoelastic materials (VEM) are added to structures, in order to enhance damping effects of the VEM, a constraining layer is attached. Due to the addition of the material on the system the fundamental characteristics of the systems are altered much. This paper analyzes the damping effect of the constraining layer on plate type structures numerically using the FEM software ANSYS. Experiments are conducted to validate the analytical results. The use of weightless composite materials as constraining layers has been analyzed. Results are compared with the conventional constraining layer materials. The results showed that composite materials give a better damping effect without much altering the fundamental characteristics.
Keywords: vibrations; composite; viscoelastic; plates